Adrenal Disorders, Surgical Approaches and Postoperative complications - Al- Obaidi, Safa M; Al-Aubaidi, Hadi M; Al- sarraf, Salem A; Al-gilani, Sarmad (Journal of the Faculty of Medicine Baghdad, 2007)
Backgraound: Adrenal disorders in surgical practice are presented either as hyperfunctional disorders or non functional disorders (incidentalomas). Functionally, medullary tumors (pheochromocytoma) result in excess secretion of catecholamines(l), on the other hand, functioning adrenocortical tumors could secrete excess of cortisol (Cushing syndrome), aldosterone (Conn's syndrome) or sex hormones (virilizing syndromes). (2The aim of our study is to identify and to show our experience in the surgical approach and postoperative complications of adrenal disorders.Patients & methods: This is a prospective study of 20 cases diagnosed as having adrenal disorders, admitted and evaluated in Baghdad Teaching Hospital-Medical City fromJanuary 2002 to December 2004. The data collected including age, gender, types of  clinical adrenal disorders, surgical approaches and postoperative complications.Result: Surgical excision was performed in 19 cases, eleven through anterior transabdominal approach (11/20, 55%), and eight through thoracoabdominal approach (8/20, 40%). A betteroutcome was recorded in the thoracoabdominal approach. The most common encountered surgical morbidity was hypertension (3/19, 15.8%) and hypocalcemia (3/19, 15.8%).Conclusion: Thoracoabdominal approach has better outcome especially in excising right adrenal tumor but transabdominal approach is preferable in excising a bilateral adrenalgland.